HEPATORENAL SYNDROME IN PRACTICE OF FAMILY MEDICINE DOCTOR (the criteria of diagnostics and treatment) - Savchenko, V. N.; Nikolenko, Y. J.; Sokruto, O.V.; Vovk, K.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The term «hepatorenal syndrome» (HRS) means a functional kidney pathology which manifests by oliguria, is potentially reversible and is developing in the condition of severe desease of liver, accompanied by liver failure and when there is no other reason for affection of kidneys. The main pathophysiologic mechanisms of HRS developing are: reversible kidney vasoconstriction and soft systemic vasodilation. Depending on the severity of the clinical manifestation and the prognosis of the disease there are two types of the HRS. The Ist type of HRS is an acute and rapidly developing; the IInd type of HRS is characterized by gradual (during several months) decreasing of kidneys’ function and increasing of blood creatinine level from 1,5 to 2,5 mg/dL. Conservative treatment includes entering of massive doses of albumin and vasoconstrictors (e.g. terlipressin). But only a liver transplantation can help to attain a considerable extention of life of patients with HRS.